Economic consequences of the First World War - Nikolić Srboljub; Mihajlović Milan; Epler Igor; Milanović Nikola (Trendovi u Poslovanju)
The First World War (1914-1918) marked the beginning of the 20th century as one of the most destructive conflicts in human history. This paper analyzes the economic consequences of the war, focusing on the costs, both material and in terms of human losses, the major economic crisis, as well as the mortgage and agricultural crises. The central issue examined is the economic impact of the war on the world, with particular attention to its long-term effects. The hypothesis is that the war's consequences significantly shaped the economic and social landscape of the world throughout the 20th century. By analyzing historical data, economic reports, and secondary sources from the literature, the aim was to present a comprehensive overview of the war's effects on the economy, considering direct and indirect costs, inflation, public debt, unemployment, and changes in property ownership structures. The post-war period, marked by recovery from massive financial expenditures, infrastructure destruction, and loss of the labor force, demonstrated that large-scale conflicts like the First World War not only lead to immediate economic collapse but also create far-reaching and long-lasting economic consequences, introducing the world to new challenges, problems, crises, and conflicts. This paper provides a deeper understanding of the consequences of global conflicts, emphasizing the crucial importance of peace and stability for economic development.